Heterogeneous Pancreatic Stellate Cells Are Powerful Contributors to the Malignant Progression of Pancreatic Cancer - Zhang, Zhilin; Zhang, Huan; Liu, Tian; Chen, Tian; Wang, Daorong; Tang, Dong (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic cancer is associated with highly malignant tumors and poor prognosis due to strong therapeutic resistance. Accumulating evidence shows that activated pancreatic stellate cells (PSCs) play an important role in the malignant progression of pancreatic cancer. In recent years, the rapid development of single cell sequencing technology has facilitated the analysis of PSC population heterogeneity, allowing for the elucidation of the relationship between different subsets of cells with tumor development and therapeutic resistance. Researchers have identified two spatially separated, functionally complementary, and reversible subtypes, namely myofibroblastic and inflammatory PSCs. Myofibroblastic PSCs produce large amounts of pro-fibroproliferative collagen fibers, whereas inflammatory PSCs express large amounts of inflammatory cytokines. These distinct cell subtypes cooperate to create a microenvironment suitable for cancer cell survival. Therefore, further understanding of the differentiation of PSCs and their distinct functions will provide insight into more effective treatment options for pancreatic cancer patients.